INTERTEXTUAL AND BOUNDARY-CROSSING MONSTROSITY IN WILLIAM BURROUGHS’ NAKED LUNCH - Michele Russo (European Scientific Journal, ESJ, 2015)
The new orientations set by the late 50s American writers have marked new features and peculiarities in the definition of what can be considered as “monstrous”. It would appear that such writers realized how enigmatic monstrosity is, since it is a “fluid” and “slippery” entity and it hides everywhere. Among the different forms of monstrosity that criticism has pinpointed and defined up-to-date, my paper means to analyze the subtle relationships between inner and outer monstrosity in W. Burroughs’ The Naked Lunch (1959). Such inner/outer relationships will be discussed through the consideration of the intertextual and topological characteristics of monstrosity in the novel. Not only do I intend to emphasize the monstrous entity represented by drugs in the book, but I also mean to locate the role of spatial and linguistic elements in the postmodern definition of monstrosity. I will focus on the connections between the protagonists’ changing personalities and the borders they cross, as an inverse Dantesque journey into the underworld. The crossing process of Interzone, as well as the “camouflaging” course of changing personalities, will be revisited by taking into account Derrida’s theories about anarchy and deconstructionism, as well as his concept of the “impossible possibility” of the events, which will analyze the visceral meanings of the “cutup” images in the book. As to the boundary-crossing process, the paper means to interpret, by using Lotman’s spatial theories, the crossing of the different spaces as deconstructing and reassembling moments of further meanings in the narrative architecture of the book itself.